Tantangan pendidikan Agama Islam di era globalisasi - Aisy, Salwatul (Maliki Interdisciplinary Journal, 2024)
Islamic Religious Education (PAI) is a vital component in shaping the identity and morality of Muslims. By integrating religious values ​​into the educational curriculum, PAI not only aims to teach religious knowledge, but also to shape the character of students so that they are in accordance with Islamic teachings. Related Arabic terms, such as ta’lim, ta’dib, and tarbiyah, describe various dimensions of this educational process, with ta’dib considered most appropriate in the context of character education. In the midst of increasingly complex globalization challenges, PAI must face various issues that can damage Islamic values, including a decline in morals and difficulties in absorbing knowledge. In this context, an innovative approach is needed to overcome these challenges. Strategies such as increasing time allocation for religious studies, curriculum reform that is more responsive to current needs, and increasing professionalism among teaching staff are crucial. Through this effort, PAI is expected to be able to produce a generation of Muslims who are not only knowledgeable, but also have a strong commitment to ethical and moral values ​​in facing modern challenges.